2013
DOI: 10.1089/scd.2012.0379
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-RGD Peptides Increase the Adenoviral Transduction of Human Mesenchymal Stem Cells

Abstract: Human mesenchymal stem cells (hMSCs) have been extensively explored for drug delivery applications due to their safety, immunomodulatory properties, and ability to differentiate into new tissues. The experiments presented in this study were designed to determine peptide-based mechanisms to increase the adenoviral transduction of hMSCs for the purpose of improving their capacity as drug delivery vehicles. Specifically, we demonstrated that cyclic-RGD peptides increased the internalization of adenoviruses into M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
(48 reference statements)
2
5
0
Order By: Relevance
“…Previous studies have demonstrated that, in the absence of protein coatings, RGD peptides presented on surfaces promote hMSC adhesion, proliferation, and viability, 7678 and simply treating hMSCs with soluble RGD significantly increases adenoviral endocytosis and subsequent transgene expression. 79 Furthermore, fibroblast growth factor has been shown to promote proliferation, inhibit apoptosis, and reduce oxidative stress in hAMSCs, 80 and fibroblast growth factor-derived peptides have been conjugated to nucleic acid-complexing polymers 81 as well as viral vectors 82 to facilitate receptor-mediated endocytosis and subsequent transgene expression. Moreover, the cell penetrating R9 peptide on ECM mimetic substrates likely activates endocytic pathways in hMSCs to increase SMD transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that, in the absence of protein coatings, RGD peptides presented on surfaces promote hMSC adhesion, proliferation, and viability, 7678 and simply treating hMSCs with soluble RGD significantly increases adenoviral endocytosis and subsequent transgene expression. 79 Furthermore, fibroblast growth factor has been shown to promote proliferation, inhibit apoptosis, and reduce oxidative stress in hAMSCs, 80 and fibroblast growth factor-derived peptides have been conjugated to nucleic acid-complexing polymers 81 as well as viral vectors 82 to facilitate receptor-mediated endocytosis and subsequent transgene expression. Moreover, the cell penetrating R9 peptide on ECM mimetic substrates likely activates endocytic pathways in hMSCs to increase SMD transfection.…”
Section: Discussionmentioning
confidence: 99%
“…20 For instance, a recent study showed that cRGD significantly increased the affinity for v3 integrin when compared to its linear counterpart. 21…”
Section: Discussionmentioning
confidence: 99%
“…20 For instance, a recent study showed that cRGD significantly increased the affinity for v3 integrin when compared to its linear counterpart. 21 Importantly, modification of the peptide backbone requires unfolding of the nanoscale bioactive molecular aggregations in order to fully permit their respective functions while simultaneously preventing any compromise of stability of the SAP structure in a physiological environment. Considering bioactive peptide motifs can conjugate RADA 16 at the C-terminus, 16 a recent study has optimized the linkage approach of motif peptides with the backbone sequence.…”
Section: Functional Motif-enhanced Sapnh Forms a Designer 3d Ecm For mentioning
confidence: 99%
“…Cyclic-RGD peptides can be used to improve the transduction efficacy of Ad vectors in vitro . Human mesenchymal stem cells can be efficiently transduced by using a GFP-expressing Ad vector in presence of cyclic-RGD peptides [ 125 ].…”
Section: Re-targeting Of Ad Vectorsmentioning
confidence: 99%